Telaah Sistem Tata Kota Kerajaan Majapahit Dalam Kakawin Nagarakrtagama - Teguh Fatchur Rozi; Misbahul Munir; Dina Maulidia (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
Kakawin Nagarakrtagama is a classic Javanese literary work written by Mpu Prapañca around the 14th century. Kakawin Nagarakrtagama is the main reference for researchers to reveal the development of the Majapahit Kingdom until the reign of King of Hayam Wuruk. This study aims to determine the Majapahit Kingdom's urban planning system recorded in Kakawin Nagarakrtagama. This study uses qualitative research methods based on literature (1) Kakawin Desawarnnana uthawi Kakawin Nagarakrtagama: The Golden Age of Majapahit composed by Riana (2009) and (2) Kakawin Nagarakertagama composed by Damaika, et al (2016). The results of this study are the Majapahit urban planning system recorded in Kakawin Nagarakrtagama including the layout of the premises and buildings: (1) Citadel made of red bricks, (2) Majapahit City Gate, (3) Village halls; gate; and gazebo, (4) Field of Watangan, (5) King of Majapahit Residence, (6) King and Governor of Gajah Mada's family residence, (7) Governor of Gajah Mada residence, (8) Palace officials residence, (9) The residence of the Shiva religious leaders as well as the Buddhist leaders, and (10) A place for settlement of the people. Overall, it can be seen that Kakawin Nagarakrtagama records well the Majapahit Kingdom's urban planning system since the time of its establishment until its golden age.